Profile Analysis of Sustainability Awareness of High School Students Related to Food Waste Issues in Magelang, Central Java - Pengestuti, Dian; Paidi; Subiantoro, Agung Wijaya; Pratama, Anggi Tias (Universitas Tidar, 2024)
Sustainability awareness has become an increasingly important aspect of global education, especially in the face of environmental challenges. This approach to education with sustainable principles is needed to educate the current generation to meet their needs without risking the next generation, including the issue of food waste. The purpose of this study is to describe the profile of sustainability awareness in high school students related to the issue of food waste. This research used a qualitative descriptive method. The instrument used was a questionnaire developed from three aspects of sustainability awareness: behavior and attitude awareness, emotional awareness, and sustainability practice awareness. The results of filling out the questionnaire were analyzed by determining the mean and percentage and then categorizing the level of sustainability awareness. The results showed that 56% of students have awareness related to the issue of food waste at a moderate level. So, it can be concluded that students have an awareness of the value of sustainability at an emotional level without practicing it in everyday life.